Pelatihan Produksi Program Berita dan Tayang Bincang untuk Televisi bagi Siswa-siswi di Madrasah Aliyah Negeri 1 Karanganyar - Erwin Kartinawati; Erna Indriastiningsih; Dahlan Susilo (Universitas Prof. Dr. Hazairin, SH, 2020)
The Training for the Production of News Programs and Talk Show on Television for Students at Madrasah Aliyah Negeri 1 Karanganyar The digital era makes it easier for humans to get information. Information provision is now no longer dominated by the mainstream media. Ordinary people can now provide information to the public by utilizing social media and other internet-based channels, such as YouTubers, citizen journalists, and other content creators. Unfortunately, they have not fully mastered the ability to produce standard information to fulfill the public's right to obtain accurate, responsible information, referring to existing ethics of information. This training was expected to provide solutions to the above problems. The determination of students as training participants was due to their much more significant curiosity and energy to do creative things to provide more incredible benefits. The benefits are not only for the students but can also be picked by society. The training was conducted at Madrasah Aliyah Negeri 1 Karanganyar, Central Java. As a result, the students at Madrasah Aliyah Negeri 1 Karanganyar were able to produce audio-visual based works, especially in the form of television news programs and talk shows according to broadcasting standards.